Role of Macrophage Colony-Stimulating Factor Receptor on the Proliferation and Survival of Microglia Following Systemic Nerve and Cuprizone-Induced Injuries - Pons, Vincent; Laflamme, Nataly; Préfontaine, Paul; Rivest, Serge (Frontiers in Immunology, 2020)
Microglia are the innate immune cells of the CNS and their proliferation, activation and survival have previously been shown to be highly dependent on macrophage colony-stimulating factor receptor (CSF1R). Here we investigated the impact of the receptor in such processes using two different models of nerve injuries, namely hypoglossal axotomy and cuprizone-induced demyelination. Both models are associated with a robust microgliosis. The role of CSF1R was investigated using the gene deletion Cre/Lox system, which allows the conditional knock-out following tamoxifen administration. We found that after 5 weeks of cuprizone diet that CSF1R suppression caused a significant impairment of microglia function. A reduced microgliosis was detected in the corpus collosum of CSF1R knock-out mice compared to controls. In contrast to cuprizone model, the overall number of Iba1 cells was unchanged at all the times evaluated following hypoglossal axotomy in WT and cKO conditions. After nerve lesion, a tremendous proliferation was noticed in the ipsilateral hypoglossal nucleus to a similar level in both knock-out and wild-type groups. We also observed infiltration of bone-marrow derived cells specifically in CSF1R-deficient mice and these cells may compensate in part for the deletion of CSF1R signaling pathway in resident microglia. Taking together our results suggest a different role of CSF1R in microglia depending on the model. In the pathologic context of cuprizone-induced demyelination CSF1R signaling pathway is essential to trigger proliferation and survival of microglia, while this is not the case in a model of systemic nerve injury. M-CSF/ CSF1R is consequently not the unique system involved in microgliosis following nerve damages.